The relationships between onboarding program and newcomers’ turnover intention : the role of organizational identification as mediator - Kannaki Narayansany,; Rosmah Mat Isa, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Research on turnover intention is gaining momentum again as Gen Y and millennials have dominated the workforce. While a growing body of work provides strategies on retaining them, not much is known about the importance of organizational identification in influencing turnover intention. To address this gap, this study investigates the role of organizational identification as mediator in the socialization—turnover specifically between onboarding program and turnover intention. Questionnaire survey were distributed to newly recruited employees who have less than 2 years working experience in ICT industry. A total of 320 samples were analyzed using PLS-SEM version 3.3.2. The results revealed that organizational identification significantly mediate the relationship between effective onboarding program and turnover intention. Theoretically, the present study contributed to knowledge by providing support for the significant role of organizational identification in reducing turnover intention. This study also contributes to the understanding on the importance of enhancing onboarding program as organization socialization mechanism in retaining newcomers. Practically, the organization should emphasise on onboarding program as it enables the newcomers to equip themselves with knowledge about the organization and the job-related tasks, but most importantly facilitate the development of organizational identification that stems from social relationship and sense of self-belongingness among the newcomers, so that they can become effective organizational members, which in turn may reduce their turnover intention.